Stature and skeletal maturation of two cohorts of Australian children and young adults over the past two decades - Ranjitkar Sarbin; Lin Ni-Hung; Macdonald Ross; Taylor Jane A.; Townsend Grant C. (Sciendo, 2023)
Assessment of growth and maturation in humans has implications in the diagnosis and treatment of growth disorders and in determining timing of orthopaedic interventions.